2016
DOI: 10.3329/bjvm.v14i1.28832
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Toxicity and Efficacy of Crude Aqueous Extract of Carica Papaya Leaf Against Trypanosoma Brucei

Abstract: The aqueous extract of Carica papaya leaf was evaluated for its phytochemistry, acute toxicity and in vitro antitrypanosomal efficacy in this study. A total of 15 albino rats grouped into 5(A-E) of 3 rats each were intraperitoneally treated with graded doses of 100, 200, 400, 800mg/kg body weight of the aqueous extract and observed for 24 hours for clinical signs and death. The calculated median lethal dose (LD50) was 600mg/kg body weight, with clinical signs of sluggishness, awkward pasture, loss of appetite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This study revealed the presence of important phytochemicals like saponins, reducing sugar, alkaloids, terpenoids, tannins, anthraquinones, flavonoids, cardiac glycosides and phenolic compounds in the methanolic leaf extract of Carica papaya. The study is in line with the reports of a number of authors that showed that active phytochemicals like: phenolics, alkaloids, steroids, saponins, phlabotannins, amino acids, flavonoids etc are present in the different extract of Carica papaya [49][50][51]. Studies have shown [43].…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed the presence of important phytochemicals like saponins, reducing sugar, alkaloids, terpenoids, tannins, anthraquinones, flavonoids, cardiac glycosides and phenolic compounds in the methanolic leaf extract of Carica papaya. The study is in line with the reports of a number of authors that showed that active phytochemicals like: phenolics, alkaloids, steroids, saponins, phlabotannins, amino acids, flavonoids etc are present in the different extract of Carica papaya [49][50][51]. Studies have shown [43].…”
Section: Discussionsupporting
confidence: 91%
“…These finding is in agreement with [22], findings which showed LD 50 of C. papaya seed above 5000 mg/kg of body weight of rat. Biu et al [6] also reported the lethal dose of aqueous extract C. papaya leaf to be safe at 1000 mg/kg.…”
Section: The Mean Lethal Dose (Ld 50 ) Of Methanolic Extracts the Fractions Of Carica Papaya Seedsmentioning
confidence: 98%
“…The few registered trypanocides are toxic and often associated with severe side effects [4]. The economic importance of the disease is often characterized by increasing anemia, induce oxidative stress, inflammation, suppress immune system, poor reproductive performance, poor lactation, weakness, extreme emaciation and eventually death [5][6][7]. The most pathogenic trypanosomes belong to the Vivax group (Duttonella), congolense group (Nannomonas) and the brucei group (Trypanozoon) subgenera.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnoveterinary medicine using plant extracts continues to provide health coverage for over 80% of the world's population, especially in the developing countries including Nigeria (WHO, 2002). Some studies on the use of plant extracts against ticks have been conducted in Pretoria, South Africa (Thembo et al, 2010); Nigeria (Biu et al, 2013;2014); Iran (Pirali-Kheirabadi and Teixeira da Silva, 2011);Brazil (Giglioti et al, 2011);Burkina Faso (Kabore et al, 2012); Egypt (Abdel-Shafy and Zayed, 2002) and India (Sanis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%